The Democratic Socialism Concept - kenaphom, sanya; Supsin, Jirayu; suktam, Wanchai (The Journal of International Buddhist Studies College, 2023)
The discussion within the paper delves into the intricate concept of democratic socialism, elucidating its overarching objectives in establishing a socio-economic framework that is characterized by equity and justice. Democratic socialism, as expounded upon, endeavors to foster a more egalitarian distribution of the benefits derived from production among individuals actively involved in the production process, thereby mitigating disparities in income and wealth prevalent within the societal fabric. Moreover, it advocates for the extension of democratic principles beyond their conventional political spheres, encompassing domains such as the workplace and the broader economic landscape. Within this paradigm, proponents of democratic socialism endorse a diverse array of methodologies aimed at attaining social ownership, ranging from governmental control of industries and resources to the promotion of worker cooperatives. The fundamental aspiration underpinning democratic socialism is the diminution of economic disparities, the guarantee of universal access to fundamental services, and the establishment of a more participatory and equitable economic structure.